Literacy Syllabus Evaluation through Needs Analysis of English for Specific Purposes - Putri, Nindya Pradanitra; Indrawati, Ni Luh Ketut Mas (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p02, 2020)
With its unique and progressive approach on education, Green School High School Literacy Syllabus shall be evaluated from an ESP perspective and there is currently no research about it. The aim of this study is to find out what language skills the students think they need and help determine if the existing syllabus at Green School has adequately addressed the needs using qualitative-quantitative methods. Through questionnaires, this study uses Hutchinson-Water's theory of target needs and learning needs. After careful evaluation, the findings suggest that the syllabus has not addressed the Needs sufficiently. Out of 86 subskills, there are only 38 subskills addressed sufficiently.  In this context-specific study, there are several implications to be drawn.